Analyses on Though-Bolts Type Wooden Beam-Column Joints Subjected to Rotational Moment - Kohei Komatsu (Wood Research Journal, 2010)
This paper introduces an examples of analyses on the elasto-plastic behavior of so-called “through-bolts type” wooden beam-column steel joints which are widely used in modern wooden residential houses recent in Japan. The analyses were done on two parts, one of which was “glulam column-steel gusset joint” where column and gusset are connected by using “though bolts” and the other part was “steel gusset-glulam beam joint” where gusset and beam are connected by using drift pins. By the theoretical analyses, initial stiffness, yielding moment and second stiffness were derived so as to include various parameters in a closed form. Full scale experiments were also carried out using three replications on two different types of test specimens. Comparisons between theoretical predictions and experimental observations showed good agreements.